2016
DOI: 10.1002/jmri.25326
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of rapid whole body and compartmental fat volume quantification on a widebore 3T MR system in normal-weight, overweight, and obese subjects

Abstract: , Test-retest reliability of rapid whole body and compartmental fat volume quantification on a widebore 3T MR system in normal-weight, overweight, and obese subjects, 2016 ABSTRACT PurposeTo measure the test-retest reliability of rapid (< 15 min) whole body and visceral fat volume quantification in normal and obese subjects on a wide bore 3T MR system and compare with conventional manual segmentation. Materials and MethodsThirty participants (BMI 20.1-48.6 kg/m 2 ) underwent two whole body MRI examinations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 41 publications
(56 reference statements)
2
25
1
Order By: Relevance
“…In a first analysis of regional muscle volume, Thomas et al [68] showed that the limits of agreement (the 95 % confidence interval of test-retest differences) between whole-body muscle measurements was as low as -0.35 L to 0.2 L. There was also a good agreement with manual segmentations. In a second analysis of the images, that focused on AT quantification, Newman et al [70] found no significant difference in adipose volume between fat-referenced volumetry and manual segmentation of magnitude images. Furthermore, the reliability of the measurements did increase with fat-referenced volumetry.…”
Section: Validation Of Fat-referenced Mri-based Body-composition Analmentioning
confidence: 99%
See 4 more Smart Citations
“…In a first analysis of regional muscle volume, Thomas et al [68] showed that the limits of agreement (the 95 % confidence interval of test-retest differences) between whole-body muscle measurements was as low as -0.35 L to 0.2 L. There was also a good agreement with manual segmentations. In a second analysis of the images, that focused on AT quantification, Newman et al [70] found no significant difference in adipose volume between fat-referenced volumetry and manual segmentation of magnitude images. Furthermore, the reliability of the measurements did increase with fat-referenced volumetry.…”
Section: Validation Of Fat-referenced Mri-based Body-composition Analmentioning
confidence: 99%
“…This evaluation has however become outdated as both reference methods have been upgraded, and the water-fat swaps seen in paper I have become less common. The PSR algorithm has also been successfully used in a range of studies [32,[68][69][70][71][72][73][74][75][76][77][78]. These studies did not directly evaluate the performance of PSR.…”
Section: Validation Of Phase-sensitive Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations